The Value of Omega-3 Fatty Acids in the Prevention of Heart Rhythm Disorders - V. I. Podzolkov; A. I. Tarzimanova (Столичная издательская компания, 2020)
One of the trends in modern cardiology is the use of omega-3 polyunsaturated fatty acids (ω-3 PUFA) in the prevention of heart rhythm disorders and the prevention of sudden cardiac death. In experimental studies, it was found that ω-3 PUFAs have a variety of pleiotropic effects: they reduce the formation of oxygen radicals, reduce reperfusion complications, reduce the level of thromboxane and platelet aggregation, and improve endothelial function. The ability of ω-3 PUFA to have an anti-inflammatory effect, which includes the inhibition of leukocyte chemotaxis, the expression of adhesion molecules, the formation of eicosanoids and biologically active substances with powerful anti-inflammatory properties. One of the most significant effects of ω-3 PUFA can be considered their anti-atherogenic effect. Antiarrhythmic properties of го-3 PUFA are associated with the effect on the ion channels of cardiomyocytes, they are able to activate "slow" calcium channels, increase the activity of Ca2+/Mg2+-ATPase and reduce the work of sodium channels. In animal experiments, it has been shown that in conditions of ischemia or adrenergic stimulation, ω-3 PUFA stabilizes the cardiomyocyte membrane, can increase the duration of the effective refractory period, and prevent the development of various heart rhythm disorders. Clinical studies have shown that the administration of ω-3 PUFA in addition to standard treatment reduces the risk of new cases of atrial fibrillation, ventricular arrhythmias and sudden cardiac death.